TRAINING FUTURE ECONOMISTS IN THE FIELD OF PROFESSIONAL FOREIGN LANGUAGE COMMUNICATION ASTHE PROBLEM OF COMPARATIVE PEDAGOGY - Мудрая, Елена (Modern engineering and innovative technologies, 2019)
The article describes the training of future economists in the field of professional foreign language communication as a problem of comparative pedagogy.